Conocimientos de cuidados paliativos en el personal de enfermería del Hospital Oncológico Solca-Loja. - Acaro Jaramillo, Karla Paola (2017)
Palliative care is those that are provided to improve the quality of life for patients and families facing life threatening illnesses, through relief from suffering, treatment of pain and other physical, psychosocial and spiritual problems. It is estimated that every year more than 20 million patients need palliative care at the end of life. The interest in care of this type has increased in health professionals, however less than 15% have been trained in this subject in undergraduate education. Resources and experience are limited. The present study is a descriptive study whose purpose was to determine the level of knowledge of palliative care in the nursing staff of the SOLCA-Loja Oncology Hospital, the instrument used for data collection was the survey and the population to be investigated Were 62 nurses and auxiliaries. The results obtained indicated an equal percentage of "high" and "low" knowledge for pain control and symptom management, knowledge for spiritual care is "regular" in terms of individualized care depending on the patient's beliefs and how Part of the palliative care, Knowledge about family care and psychosocial care is "high". Conclusion: The level of knowledge of palliative care in nursing staff at SOLCA - Loja Oncology Hospital is high related to pain control, symptom management, family care and psychosocial care. However it is regular in the spiritual care. KEY WORDS: Palliative Care, nursing staff, knowledge